The interaction of Hg2+ and trivalent ions with two new fluorescein bio-inspired dual colorimetric/fluorimetric probes. Issue 23 (19th May 2016) - Gonçalves, A. C.; Pilla, V.; Oliveira, E.; Santos, S. M.; Capelo, J. L.; Dos Santos, A. A.; Lodeiro, C.
Abstract : Two new bio-inspired fluorescein derivatives were successfully synthesized and both the compounds showed a "turn on" fluorescence in the presence of trivalent (Al 3+, Fe 3+, Ga 3+, Cr 3+ ) and Hg 2+ metal ions, forming mononuclear complexes in acetonitrile. Abstract : Two new luminescent compounds containing fluorescein–amino acid units have been designed and synthesized via an ester linkage between a fluorescein ethyl ester and Boc-Ser(TBDMS)-OH or Boc-Cys(4-MeBzl)-OH, and their photophysical properties have been explored. The optical response of both compounds (2 and3 ) towards the metal ions Na +, K +, Hg +, Ag +, Ca 2+, Co 2+, Ni 2+, Cu 2+, Zn 2+, Cd 2+, Pb 2+, Hg 2+, Al 3+, Fe 3+, Ga 3+ and Cr 3+ was investigated in pure acetonitrile and in acetonitrile/water mixtures. A strong CHEF (Chelation-Enhanced Fluorescence) effect was observed with all the trivalent metals and Hg 2+ ions in both solvents. UV-vis absorption, steady state and time resolved emission spectroscopy methods were employed. The results show the formation of mononuclear complexes with Al 3+, Fe 3+, Ga 3+, Cr 3+, and Hg 2+ . Theoretical calculation using Density Functional Theory was performed in order to obtain atomistic insights into the coordination geometry of Al 3+ and Hg 2+ to the fluorescein3, which is in accordance with the experimental stoichiometry results obtained in the Job's plot method. Among the active cations, the minimum detectable amount is under 1 μM for most of the cases in both absorption and fluorescence spectroscopy methods.